Cost Utility of cognition-enhancing interventions for individuals with first-episode psychosis: a naturalistic evaluation - Nicholas J. K. Breitborde; Emily K. Bell; Cindy Woolverton; Jacob G. Pine; Heather Waslter; Aubrey M. Moe (Cost Effectiveness and Resource Allocation, 2021)
Abstract Background Although effective treatments are available to address the cognitive deficits experienced by individuals with first-episode psychosis, provision of such treatments within Coordinated Specialty Care (CSC) programs is rare. One factor that may contribute to this is uncertainty about the cost implications of providing cognitive-enhancing treatments within the American mental healthcare system. The aim of this study is to complete a naturalistic evaluation of the cost utility of incorporating two different cognitive-enhancing interventions within an American CSC program. Methods Participants included 66, predominately white (75.38%), individuals with first-episode psychosis (19 women and 47 men) with a mean age of 22.71 years. Quality adjusted life years (QALYs) and cost of care were tracked among these individuals during their participation in a CSC program. These data were compared among three groups of participants during their first six months of care: (i) individuals who participated in metacognitive remediation therapy (MCR), (ii) individuals who participated in computerized cognitive remediation (CCR), and (iii) individuals who participated in no cognitive-enhancing intervention. Results Participation in MCR, but not CCR, was associated with larger gains in QALYs than participation in no cognitive-enhancing intervention within a CSC program. Moreover, data support the cost utility of MCR as compared to CCR or no-cognitive enhancing intervention within a CSC program. Conversely, CCR did not appear to be a cost-effective addition to CSC services. Conclusions Our results highlight the potential cost utility of incorporating MCR within CSC programs for individuals with first-episode psychosis. However, given study limitations, these results should be interpreted cautiously until replicated by large, randomized controlled trials. Trial Registration ClinicalTrials.gov Identifier NCT01570972, registered April 4, 2012, Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT01570972?term=breitborde&draw=2&rank=6 .